Giving Credit Where Credit Is Due - Altbach, Philip G (International Higher Education, 2016)
Awarding credit for publication, for prizes such as the Nobels, and other aspects of academic work has become more complicated. How is credit handled for articles that have 1,000 authors? Are Nobel prizes national or individual accomplishments? This article considers the complexities of awarding credit for academic work.